MC12: How to make the WTO relevant in the middle of a food price crisis - Glauber, Joseph W.; Laborde Debucquet, David; Mamun, Abdullah; Olivetti, Elsa; Piñeiro, Valeria (International Food Policy Research Institute, 2023)
The World Trade Organization’s 12th Ministerial Conference (WTO MC12) takes place June 12–15, 2022, in Geneva — two years after the pandemic forced members to postpone the meeting’s original schedule. In that time span, the world has changed and the need for multilateral approaches to tackling international trade issues has become even more acute. The Russia-Ukraine war has highlighted a variety of unresolved trade issues as poor countries struggle to meet food security needs amid tightening global supplies and high prices, exacerbated by a conflict whose two participants account for 12% of world agricultural exports (on a calorie basis) and threatening 20% of global fertilizer trade. Two issues of particular concern amid the growing food crisis are export restrictions and public stockholding programs. Agricultural export restrictions have been a major topic in global trade negotiations since the food price crisis of 2007/08, when many countries imposed such measures, particularly on food grains like wheat and rice. Now it is happening again: Since Russia’s invasion of Ukraine in February 2022, 23 countries have imposed export restrictions affecting over 16% of global agricultural trade (on a calorie basis).